Resolution of Inflammation after Skeletal Muscle Ischemia–Reperfusion Injury: A Focus on the Lipid Mediators Lipoxins, Resolvins, Protectins and Maresins - Barnig, Cindy; Lutzweiler, Gaetan; Giannini, Margherita; Lejay, Anne; Charles, Anne-Laure; Meyer, Alain; Geny, Bernard (Antioxidants, 2022)
Skeletal muscle ischemia reperfusion is very frequent in humans and results not only in muscle destruction but also in multi-organ failure and death via systemic effects related to inflammation and oxidative stress. In addition to overabundance of pro-inflammatory stimuli, excessive and uncontrolled inflammation can also result from defects in resolution signaling. Importantly, the resolution of inflammation is an active process also based on specific lipid mediators including lipoxins, resolvins and maresins that orchestrate the potential return to tissue homeostasis. Thus, lipid mediators have received growing attention since they dampen deleterious effects related to ischemia–reperfusion. For instance, the treatment of skeletal muscles with resolvins prior to ischemia decreases polymorphonuclear leukocyte (PMN) infiltration. Additionally, remote alterations in lungs or kidneys are reduced when enhancing lipid mediators’ functions. Accordingly, lipoxins prevented oxidative-stress-mediated tissue injuries, macrophage polarization was modified and in mice lacking DRV2 receptors, ischemia/reperfusion resulted in excessive leukocyte accumulation. In this review, we first aimed to describe the inflammatory response during ischemia and reperfusion in skeletal muscle and then discuss recent discoveries in resolution pathways. We focused on the role of specialized pro-resolving mediators (SPMs) derived from polyunsaturated fatty acids (PUFAs) and their potential therapeutic applications.